Activated carbon based adsorptive natural gas storage - Kon, Suh Kee; Kamarudin, Khairul Sozana Nor; Mat, Hanapi (2005)
Natural gas is one of the major clean fuels that receive attention as it possesses cost competitive and lower emission features compared to gasoline. Liquefied natural gas (LNG) and compressed natural gas (CNG) have been applied in natural gas vehicles, while adsorbed natural gas (ANG) and natural gas hydrate (NGH) are still being studied in order to reduce the capital and operating costs. The main challenge that confronts ANG vehicle is the extension of driving range. Studies on gas storage capacity, delivery of natural gas and future research directions of activated carbon based adsorbents, aiming to achieve the stored volumetric efficiency correspond to the current CNG system, have been reviewed.